Effect of standardized management on improvement of calcium and phosphorus metabolism disorders in hemodialysis patients - XIA Xiao-rong; GAO Xin-lu; XIA Qing; WU Wei; XIA Li-juan; WU Mei-jun (Linchuang shenzangbing zazhi)
Objective To explore the effect of standardized management on improving calcium and phosphorus metabolism disorders in maintenance hemodialysis patients. Methods From June 2016 to June 2017,54 cases of maintenance hemodialysis patients with serum phosphorus >1. 78 mmo L/L in the nephrology department of the Affiliated Hospital of Jiujiang University were selected,of which 36 were male,18 women,25 ～ 81 years old,with an average of( 56. 5 ± 15. 3)years. The patients were enrolled in the control group. Standardized management is carried out jointly by kidney specialist,hemodialysis Specialist( dialysicians and nurses) and dietitians. Dietitians guide patients to diet and give a low phosphorus diet; specialists give individualized treatment based on the patient’s condition,such as the use of phosphorus binder,and hemodialysis Specialist give adequate dialysis. The serum phosphorus,serum calcium,total parathyroid hormone( i PTH),calcium and phosphorus product,serum albumin and so on were observed for 3 months and 6 months after standardized management,and the changes of these indexes were compared before and after the standard management. Results After 3 months of administration,the serum phosphorus,calcium and phosphorus products decreased significantly compared with those before management,and thedifference was statistically significant( P < 0. 05). management after 6 months,serum phosphorus and calcium phosphorus product were significantly decreased,compared with before,the difference was statistically significant( P < 0. 01); management,the level of i PTH was a downward trend,6 months after the i PTH level was before the difference was statistically significant( P < 0. 05),serum calcium,serum albumin did not change significantly,compared with before,the difference was not statistically significant( P > 0. 05). Conclusions The standardized management of maintenance hemodialysis patients; to a certain extent improve calcium and phosphorus metabolism,prevent the calcium and phosphorus metabolism disorders caused by malnutrition,reduce the incidence of multiple organ damage and cardiovascular disease,prolong the survival time of patients,improve the quality of life of patients.